Um olhar sobre a política de formação de professores de Física no Brasil - Santos, Gicélia Maria de Oliveira (2018)
This research had the objective of analyzing the result of the federal public policies for the formation of Physics teachers for the basic education of Brazil. Among the relevant policies, the Institutional Scholarship Initiative Program (PIBID) received special attention. This research was based on the statistics on teachers of Physics in Brazil and on the concept of teaching knowledge of Tardif (2012). The methodological procedures adopted were divided into two actions: the first one was presented as a quantitative research of the type documentary study carried out from the statistical data on the titration of physics teachers of basic education and their training in higher education, which were collected in the Statistics Synopsis of Higher Education published by the National Institute of Studies and Educational Research Anísio Teixeira and in the Platform CultivEduca and analyzed through Descriptive Statistics; and the second comprised a qualitative case-study study, represented by the figures of the area coordinating teacher and the supervising teacher of PIBID, whose opinions were collected through semi-structured interviews and analyzed through the thematic analysis of Bardin (1977). The analysis showed that in general, physics teachers are, in fact, mathematics teachers or other professionals who are teaching without any methodological or theoretical support. The number of vacancies in the degree courses in Physics has grown a lot and the number of candidates, even more. However, this growth was not accompanied by the increase in the number of tickets, which made the growth of idle seats represent the most significant statistic. These courses also showed an increase in evasion rates, such that the average of the evasion rate estimated by the Organization for Economic Cooperation and Development (OECD) model, the most accurate in the study, was 60.2%. The research subjects pointed out that some actions of the PIBID can reduce idle vacancies, evasion and retention in these courses. In addition, the activities carried out in PIBID can mobilize diverse teaching knowledge, benefiting the graduates and the educational institutions involved. The data show that the problem of the lack of physics teachers with the specific formation continues. Thus, in order for the 15th Goal of the National Education Plan (2014-2024) to be achieved, more investment is needed in public policies that promote a growth in the attractiveness of the teaching profession and the permanence of the graduates in the classroom.